Oral Squamous Cell Carcinomas and Expression of Inflammatory Markers - Ruth Tramontani Ramos; Karla Malta Ferreira; Lucio Souza Gonçalves; Luciana Armada; André Luiz da Rocha Azevedo; Teresa Cristina Ribeiro Bartholomeu dos Santos; Mayra Stambovsky Vieira; Alexandre Marques Paes Silva; Dennis de Carvalho Ferreira; Marcia Gonçalves Ribeiro (Editorial Ciencias Médicas, 2023)
Objectives: To describe the clinical and histopathological information of oral squamous cell carcinomas an oral pathology clinic of a private university in Rio de Janeiro state, Brazil (1998−2017) and to evaluate the immunoexpression of some inflammatory markers (nterferon-gamma, cluster of differentiation 57, and cluster of differentiation 68). Methods: Clinical data were collected and histopathological evaluations of 183 oral squamous cell carcinomas were performed at an oral pathology clinic of a private university in Rio de Janeiro state, Brazil (1998−2017). Twenty-two paraffin blocks underwent immunohistochemistry to measure the Interferon-gamma, cluster of differentiation 57, and cluster of differentiation 68 expressions and positivity, and were classified as negative/focal, weak/moderate, or strong. Results: Thereabout 81% of the sample were male and 57% Caucasian. The average age was 58.6 years. Tongue cancers were the most prevalent (36.6%) and 48.1% had a moderately differentiated oral squamous cell carcinomas. Interferon-gamma was expressed in all cases, and 91% had the maximum degree of marking. The cluster of differentiation 68 expression had a maximum degree in 41% of the tumours, and surprisingly all of them in concomitance with the maximum Interferon-gamma-markings. cluster of differentiation 57 was strongly expressed in 45.5% of the sample. Conclusion: Oral squamous cell carcinomas was more frequent in Caucasians, in their fifth decade of life, and located on the tongue. The Interferon-gamma expression was observed in all cases, its role in the development of tumours and the concomitant expression of cluster of differentiation 68 suggests a possible differentiation for the M2 phenotype of tumours and a consequently a poor prognosis.